Sense (and) the city: From Internet of Things sensors and open data platforms to urban observatories - Vijay Kumar; Sam Gunner; Maria Pregnolato; Patrick Tully; Nektarios Georgalas; George Oikonomou; Stylianos Karatzas; Theo Tryfonas (IET Smart Cities)
Abstract Digitalisation and the Internet of Things (IoT) help city councils improve services, increase productivity and reduce costs. City‐scale monitoring of traffic and pollution enables the development of insights into low‐air quality areas and the introduction of improvements. IoT provides a platform for the intelligent interconnection of everyday objects and has become an integral part of a citizen's life. Anyone can monitor from their fitness to the air quality of their immediate environment using everyday technologies. With caveats around privacy and accuracy, such data could even complement those collected by authorities at city‐scale, for validating or improving policies. The authors explore the hierarchies of urban sensing from citizen‐to city‐scale, how sensing at different levels may be interlinked, and the challenges of managing the urban IoT. The authors provide examples from the UK, map the data generation processes across levels of urban hierarchies and discuss the role of emerging sociotechnical urban sensing infrastructures, that is, independent, open, and transparent capabilities that facilitate stakeholder engagement and collection and curation of grassroots data. The authors discuss how such capabilities can become a conduit for the alignment of community‐ and city‐level action via an example of tracking the use of shared electric bicycles in Bristol, UK.